VoR 2018
DOI: 10.32623/1.00007
|View full text |Cite
|
Sign up to set email alerts
|

Principal Coaching in Central Office Supervisory Roles: Exploring Persistent Tensions

Abstract: Scholars have increasingly focused on the practice of central office administrators. Principal supervisors, who often work in central offices, have received attention as scholars view these administrators as an essential source of support for school principals. This study employed a thematic analysis of semi-structured interviews conducted with 20 principal supervisors who participated in coaching partnership facilitated by a private, mid-sized university over three academic years. Additionally, the data set i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…It is possible that this non-directive approach is generally well-received by and useful to most principals, but that there are some who respond better to directives. While a non-directive approach is a hallmark of the predominant models of leadership coaching, research has shown that principal supervisors often "resort" to directive behaviors (Lochmiller, 2018a). Our research suggests that there may be important nuance in the appropriateness of a directive, rather than non-directive, coaching approach based on content, contextual conditions, and coach-to-principal match.…”
Section: Consistently Highly Rated Coaches Used More Non-directive Methodsmentioning
confidence: 74%
See 3 more Smart Citations
“…It is possible that this non-directive approach is generally well-received by and useful to most principals, but that there are some who respond better to directives. While a non-directive approach is a hallmark of the predominant models of leadership coaching, research has shown that principal supervisors often "resort" to directive behaviors (Lochmiller, 2018a). Our research suggests that there may be important nuance in the appropriateness of a directive, rather than non-directive, coaching approach based on content, contextual conditions, and coach-to-principal match.…”
Section: Consistently Highly Rated Coaches Used More Non-directive Methodsmentioning
confidence: 74%
“…In contrast, tools may be useful for some principals and not for others, depending on their needs, capacities, and contexts. While utilizing tools and protocols in leadership coaching is common (Lochmiller, 2018b), our finding that mixed-rated IDs more commonly cited using them than consistently highly-rated IDs did raises questions about how to best use tools and protocols to support principals. Equally important to the use of these strategies was the approach with which they are applied.…”
Section: Across Topics Consistently High-rated Ids Used Joint Work While Mixed Rated Ids Relied Upon Toolsmentioning
confidence: 88%
See 2 more Smart Citations
“…Principal support, the third and newest function of the supervisor role, builds upon the notion of evaluation for improvement by emphasizing the supervisor's use of coaching and professional development to guide principal improvement (Lochmiller, 2018; Thessin, 2019). The support function requires further shifts in supervisors’ mindsets and practices, from simply identifying and evaluating principals’ leadership performance to teaching principals how to lead effectively.…”
Section: Principal Supervisor Role Changementioning
confidence: 99%